Incidence and risk factors of functional upper airway complications of primary esthetic closed rhinoplasty in two residency programs: A 6-month preliminary prospective cohort study - Hassan Mohajerani; Fatemeh Karimi; Alireza Mohajerani; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2013)
Background: Although esthetic rhinoplasty has many advantages, it might lead to some complications as well. The literature includes scarce and severely controversial studies on these issues, and there is no research on complications of cosmetic closed rhinoplasty. In addition, some complications are not assessed after any rhinoplasty types. Besides, there is no investigation on the outcome of rhinoplasty carried out by graduate students. The purpose of this study was to determine these. Materials and Methods: In this preliminary prospective cohort study, 96 healthy patients underwent closed esthetic rhinoplasty by senior residents of otolaryngology and maxillofacial surgery at Taleghani Hospital (Tehran, 2004-2006). Afterward, at 11 follow-up sessions (the 1 st , 2 nd , 3 rd , 4 th , 6 th , 8 th , 10 th , 12 th , 16 th , 20 th , and 24 th postoperative weeks), five functional complications (hyposmia/anosmia, nasal obstruction, unpleasant voice changes, recurrent colds, and synechiae) were questioned/examined. The presence of a symptom during at least four subsequent sessions (without elimination until the sixth postoperative month) and the appearance of synechiae in any session were regarded as positive. The data were assessed using Spearman's correlation coefficient (α = 0.05). Results: The incidence rates of synechiae, nasal obstruction, unpleasant voice changes, hyposmia/anosmia, and recurrent colds were 56.25%, 37.5%, 0%, 1.04%, and 29.17%, respectively. No statistically significant relationship was found between the complications with age, gender, or the surgeon's specialty ( P > 0.05), but the correlation with home care compliance was significant (ρ = -0.29, P = 0.01). Conclusions : High complication rates were observed in both residency programs. Failure to follow home care instructions might prevent/delay recovery. Further in-depth studies are needed to assess this.